Effects of diet calcium : phosporus ratio and metabolizable energy content on development of osteochondrosis, foot bending and performance in blue foxes - Korhonen, Hannu T; Happo, Mikko; Rekilä, Teppo; Valaja, Jarmo; Pölönen, Ilpo (British society of animal science, 2005)
The study evaluates the effects of two dietary Ca : P ratios (1·5 : 1 v. 2·5 : 1) and metabolizable energy (ME) contents (17·3 MJ/kg dry matter ( DM) v. 19·2 MJ/kg DM) on the development of osteochondrosis, foot bending and performance in juvenile male blue foxes (Alopex lagopus). Four experimental groups (no. = 10 per group) were formed : (1) low energy, low Ca : P ( LELC); (2) normal energy, low Ca : P ( NELC); (3) low energy, normal Ca : P ( LENC); and (4) normal energy, normal Ca : P ( NENC). The experiment started at weaning in mid July and finished in early October. From mid August onwards, animals on the normal energy diets ( NELC, NENC) grew signi?cantly faster ( P < 0·001) than animals on the low energy diets ( LELC, LENC). The final body weights of the normal energy groups were 1·5 kg higher than those of the low energy groups ( P < 0·001). The dietary Ca : P ratio did not affect live-weight gain. Foot bending increased significantly from summer to autumn ( P < 0·001). Changes in foot bending between initial and ?nal evaluations showed that bending was significantly greater( P < 0·05) in animals on normal energy ( NELC, NENC) than on low energy diets ( LELC, LENC). Significant differences were not found in the mean degree of damage in foot and cartilage between the groups. Ulna breaking strength was significantly higher ( P < 0·05) in normal energy ( NELC, NENC) than in low energy ( LELC, LENC) animals. Ulna calcium and phosphorus concentrations of the normal Ca : P ( LENC, NENC) groups were significantly higher ( P < 0·001, P < 0·05) than those of the lower Ca : P ( LELC, NELC) groups. The bone (ulna) calcium and phosphorus concentrations tended to be higher in the normal energy ( NELC, NENC) than in the low energy ( LELC, LENC) groups (calcium P = 0·07; phosphorus P = 0·06). The bone Ca : P ratio was higher ( P < 0·001) in the normal ( LENC, NENC) than in the low Ca : P diet ( LELC, NELC) animals. The carcass weights of normal energy animals ( NELC, NENC) were signi?cantly higher ( P < 0·001) than those of low energy ( LELC, LENC) animals. The fat : dry matter ratio was higher ( P < 0·05) in normal ( NELC, NENC) than in low energy ( LELC, LENC) carcasses. We conclude that the Ca : P ratio of the diet has no effect on the development of osteochondrosis or bending of the foot. The higher body weight caused by normal as opposed to low metabolizable energy content seems, however, to increase the incidence of foot bending.
Keywords: Ko; osteokondroosi; sinikettu; ruokinta; ravitsemus